NESTER - WADAH REKREASI DAN KEBUGARAN - Jesslyn Sulaiman; Budi Adelar Sukada (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
According to Ray Oldenburg Third Place, refers to the place where people spend time between home ('first place') and place of work ('second place'). One example of a third place is a recreation center. According to Daniel D. Mclean, recreation can include a very wide variety of activities, including sports. Sports recreation is a type of sport that is intentionally done for personal gain, for fun. Life in a big city, like Jakarta, which is full of activities and routines can cause boredom and mental stress on the community. Based on data from the International Labor Organization, total working hours in a week in Jakarta increased in 2016 with a total of 32 hours compared to total working hours in 2006 of 27 hours and based on research from the Organization for Economic Co-Operation and Development (OECD), Indonesia was in position 3 with the country with the worst balance between work and life with a figure reaching 14.3%. According to a psychologist, Kartasasmita, M. Psi, work is the highest cause of stress on a person. With Jakarta's condition like that, needed a facility that can accommodate the recreational and fitness needs of the community in the form of Third Place. The aim of this project is to improve the quality of life of urban communities, in terms of physical and psychological health and fitness. The design method used is comparison which refers to the Place theory in Architecture according to Christian Norberg Schulz. The main programs offered in this project include a fitness area, sports studio, spa, sauna, hydrotherapy pool, jogging track, bicycle track, yoga & meditation park, and supporting areas such as sports retail and dining areas. AbstrakMenurut Ray Oldenburg tempat ketiga (Third Place), mengacu pada tempat di mana orang menghabiskan waktu antara rumah ('tempat pertama') dan tempat bekerja (tempat 'kedua'). Salah satu contoh tempat ketiga adalah pusat rekreasi. Menurut Daniel D. Mclean, rekreasi dapat mencakup berbagai kegiatan yang sangat luas, termasuk olahraga. Rekreasi olahraga merupakan jenis olahraga yang sengaja dilakukan untuk kepentingan pribadi, untuk bersenang-senang. Kehidupan di kota besar, seperti Jakarta yang penuh dengan aktivitas dan rutinitas dapat menimbulkan kejenuhan dan tekanan mental pada masyarakatnya. Berdasarkan data dari International Labour Organization, total jam kerja dalam seminggu di Jakarta meningkat pada tahun 2016 dengan total 32 jam dibandingkan dengan total jam kerja pada tahun 2006 yaitu 27 jam dan berdasarkan penelitian dari Organisation For Economic Co-Operation And Development (OECD), Indonesia berada di posisi 3 dengan negara yang paling buruk keseimbangan antara kerja dan kehidupan dengan angka mencapai 14,3%. Menurut seorang psikolog, Kartasasmita, M. Psi, pekerjaan merupakan penyebab stress tertinggi pada seseorang. Dengan kondisi Jakarta yang seperti itu, diperlukan sarana yang dapat mewadahi kebutuhan rekreasi dan kebugaran masyarakat berupa Third Place. Tujuan proyek ini untuk meningkatkan kualitas hidup masyarakat perkotaan, dalam hal kesehatan dan kebugaran baik fisik maupun psikis tubuh. Metode desain yang digunakan yaitu komparasi yang mengacu kepada teori Place dalam Arsitektur menurut Christian Norberg Schulz. Program utama yang ditawarkan pada proyek ini terdapat area fitness, studio olahraga, spa, sauna, hydrotherapy pool, jogging track, bicycle track, yoga & meditation park, dan area penunjang seperti sport retail dan tempat makan.